Cytotoxicity assessment and suspected screening of PLASTIC ADDITIVES in bioplastics of single-use household items. (February 2023) - Savva, Katerina; Borrell, Xavier; Moreno, Teresa; Pérez-Pomeda, Ignacio; Barata, Carlos; Llorca, Marta; Farré, Marinella
Abstract: Bioplastics made of renewable sources provide an excellent alternative to fossil-based materials. However, similar or greater quantities of plastic additives than fossil-based plastics are used in the formulations of bioplastics to improve their performance and barrier properties. Nowadays, there is an increasing concern about sources of chemical exposure. However, there is an important knowledge gap regarding complex additive mixtures, particularly in bio-based materials. In this study, we have characterised the presence of plastic additives in single-use materials (collected from retail shops in Spain), which are made of the most common bio-based biodegradable materials, poly(lactic acid) (PLA) and poly(hydroxybutyrate) (PHB), in contrast with a fossil-based plastic material that is extensively made from high-density polyethylene (HDPE). The approach consisted of the pulverization of material in the nano-micro range (100 nm-10 μm), with the materials being extracted using different solvents and ultrasonic-assisted solvent extraction (UASE). 100% of the additives in the material cannot be extracted, but since they were performed in the same condition for all materials can inform about the fingerprint of primary organics and the relative abundances between the different materials. The extracts were analysed by high-performance liquid chromatography coupled with high-resolution mass spectrometry equipped with a heated electrospray ionisation source operated in positive and negative ionisation conditions (HPLC-HESI(+/−)-HRMS), separately, using a suspect screening approach. A total number of 203 additives were tentatively identified (confidence level 2) in the bioplastics items of this study. An average of 123 plastic additives were found in PLA items and 121 in PHB items. Plasticisers were the most abundant additives; the phthalates group was the most commonly found, while 63 plastic additives were confirmed by standards and quantified. In parallel, the cytotoxicity of plastic particles in terms of cell viability and oxidative stress was studied using A549 alveolar basal epithelial cells, and the toxicity of the different extracts was also established using HepG2 adenocarcinoma cells. The main results of this study demonstrate that the plastic particles did not show a significant reduction in cell viability, but oxidative stress was significant, with PLA being the material that showed the highest effect. On the other hand, extracts of plastic particles did not show inhibition of cell viability except for HDPE extract, but the different extracts produced oxidative stress, with PLA showing the highest effect. Although the item showing the highest concentrations of additives was the extract of PLA material while also showing the most elevated oxidative stress, the low migration of toxicants from plastic materials ensures their safe use. However, this also supports the idea that bioplastics can contain many toxic substances in their formulations, some of which are unknown and should be studied in more depth. Graphical abstract: PLASTIC ADDITIVES GROUPS TENTATIVELY IDENTIFIED IN BIOPLASTICS. Image 1 Highlights: Plastic additives in bioplastics of single-use items were characterised. A total number of 123 additives were tentatively identified. Cell viability and oxidative stress of bioplastics and additives extracts were studied. Polylactic acid showed the highest oxidative stress.